Atomic Layered Titanium Sulfide Quantum Dots as Electrocatalysts for Enhanced Hydrogen Evolution Reaction. Issue 1 (25th October 2017) - Liu, Yang; Liang, Chenglu; Wu, Jingjie; Sharifi, Tiva; Xu, Hui; Nakanishi, Yusuke; Yang, Yingchao; Woellne, Cristiano F.; Aliyan, Amir; Martí, Angel A.; Xie, Banghu; Vajtai, Robert; et al.
Abstract: The overall electrocatalytic activity toward hydrogen evolution reaction for layered transition metal dichalcogenides is governed by their intrinsic activity, the corresponding density of active sites, and the electron transfer resistance. Here, nanoengineering strategies to scale down both the lateral size and thickness of layered 1T‐TiS2 powder to quantum dots (QDs) by bath sonication and probing sonication incision are employed. Uniform lateral size of 3–6 nm in the resulting QDs enhances the density of edge sites while the atomic layer thickness (1–2 nm) facilitates the electron transfer from the substrate to the edge sites. The obtained TiS2 QDs exhibit superior hydrogen evolution reaction activity over TiS2 nanosheets and MoS2 QDs prepared by the same method. The turnover frequency of TiS2 QDs with a small loading of 0.7 ng cm −2 in an optimal deposition on electrode reached ≈2.0 s −1 at an overpotential of −0.2 V versus RHE, several orders of magnitude higher than TiS2 nanosheets (0.01 s −1 ) and MoS2 QDs (0.07 s −1 ). Abstract : The nanoengineering of TiS2 to quantum dots (QDs) increases the active sites of electrocatalyst for hydrogen evolution reaction. Compared with TiS2 nanosheets and MoS2 QDs, more active sites and inherent metallicity of TiS2 QDs perform higher turnover frequency reaching to 2.01 s −1 .